Decreased SLC39A1 (Solute carrier family 39 member 1) expression predicts unfavorable prognosis in patients with early-stage hepatocellular carcinoma. Issue 1 (1st January 2021) - Zhang, Qinglin; Pan, Jiadong; An, Fangmei; Nie, He; Zhan, Qiang
ABSTRACT: Solute carrier family 39, member 1 (SLC39A1) is a member of the zinc-iron permease family and located to the cell membrane, acting as a zinc uptake transporter. However, the clinical impacts of SLC39A1 in early-stage hepatocellular carcinoma (EHCC) have not been defined. In this research, we compared the differential expression of SLC39A1 in EHCC and normal tissues based on tissue microarray, and the clinical significance of SLC39A1 in EHCC was evaluated as well. Compared with adjacent tissues, SLC39A1 was remarkably decreased in paired EHCC tissues. Besides, decreased SLC39A1 expression was significantly associated with several clinic-pathological features and serum biochemical indicators. Furthermore, Kaplan-Meier analysis exhibited that both overall survival (OS) and relapse-free survival (RFS) of patients with low expression of SLC39A1 were notably poorer than that of patients with high expression. Moreover, Cox regression analyses revealed that low expression of SLC39A1 was an independent prognostic factor for OS in patients with EHCC. Subgroup analysis also revealed beneficiary populations benefiting from the prognostic evaluation using SLC39A1 expression. Collectively, we summarized that downregulated expression of SLC39A1 is a worse prognostic factor for patients with EHCC, which can be used as a promising diagnostic and prognostic biomarker for EHCC.